Collective Cost Calculation Analysis In Determining The Cost Of Production Cv. Barokah - Nur Rizqi, Muhammad; Yudiana, Yudiana; Nisa Juliani, Citra (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2022)
The purpose of writing this thesis is to determine the calculation of the cost of goods manufactured CV. Barokah uses cost accounting calculations and finds out the amount of profit / loss obtained by the company. In this study using the relative selling value method, the authors conclude that: In calculating the joint cost allocation on CV. Barokah generates a total cost of Rp. 38,188,130. From the calculation of the joint allocation, the cost of the product was obtained, for brown bread of Rp. 972, cheese bread of Rp. 1,085, of strawberry bread of Rp. 1,108, and for peanut bread of Rp. 1,031. In calculating the profit using the relative selling value method, it generates a gross profit of Rp. 10,037,871, which consists of profit for brown bread of Rp. 2,325,470, cheese bread of Rp. 2,596,055, strawberry bread of Rp. 2,650,172, and bread peanuts amounting to Rp. 2,466,174. So that this company can determine the selling price of its products precisely and accurately, in the sense that it is neither too low nor too high.